Influence of live and artificial diets on tissue composition and trypsin activity in Penaeus japonicus larvae - Le Vay, L.; Rodríguez, A.; Kamarudin, M.S.; Jones, D.A. (Elsevier, 1993)
Penaeus japonicus larvae were reared using live food, an artificial diet or an artificial diet plus C. gracilis. Larvae from all treatments were equivalent in weight and length at the third protozoeal stage, but mysis and postlarvae from both the live food and the artificial diet plus C. gracilis treatments were significantly larger and reached metamorphosis earlier than those fed the artificial diet alone. There were significant increases in percentage nitrogen and carbon contents during development in larvae fed the live food or the artificial diet plus C. gracilis, but not of larvae fed the artificial diet alone. High growth and nitrogen and carbon retention in mysis larvae fed live food was accompanied by a drop in trypsin activity. Despite a strong trypsin response to the artificial diet, mysis larvae appear unable to assimilate sufficient dietary protein to support growth equivalent to that observed in larvae fed live food.